Strategic Management of Character Education: A Holistic Model for Fostering Socio-Religious Attitudes in an Islamic Elementary School in Indonesia - Dian; Dianing Banyu Asih; Elis Karwati Sri Mulyani; Silviana Putri; Muhammad Iksan Fahmi Nusyeha; Nadira Salsabila (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
The decline in moral values and religious internalization among elementary school students necessitates effective character education management. This study aims to describe the strategic management of character education in shaping students' socio-religious attitudes at SD Assalam Bandung, an Islamic elementary school in Indonesia. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and document analysis. The results reveal a three-phase strategic management model: (1) strategic formulation through a vision-based "Keassalaman Curriculum" integrating religious and social values; (2) implementation through systematic habituation, teacher exemplarity, and student leadership programs (Askar and Dakwah); and (3) evaluation via collaborative monitoring involving parents through the PPNP system. This integrated approach significantly improves students' social confidence and religious discipline. The study's novelty lies in applying strategic management as a holistic system in character education, addressing a gap in prior research that has focused narrowly on curriculum or pedagogy without examining integrative management processes. It offers a replicable model for Islamic elementary schools, contributing both conceptually and practically to systematic character education development. ABSTRAK Menurunnya nilai moral dan internalisasi religius pada siswa sekolah dasar memerlukan manajemen pendidikan karakter yang efektif. Penelitian ini bertujuan untuk mendeskripsikan manajemen strategis pendidikan karakter dalam membentuk sikap sosial-religius siswa di SD Assalam Bandung, sebuah sekolah dasar Islam di Indonesia. Menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui observasi, wawancara mendalam, dan analisis dokumen. Hasil penelitian mengungkap model manajemen strategis tiga fase: (1) formulasi strategis melalui "Kurikulum Keassalaman" berbasis visi yang mengintegrasikan nilai religius dan sosial; (2) implementasi melalui pembiasaan sistematis, keteladanan guru, dan program kepemimpinan siswa (Askar dan Dakwah); dan (3) evaluasi melalui pemantauan kolaboratif yang melibatkan orang tua melalui sistem PPNP. Pendekatan terpadu ini secara signifikan meningkatkan kepercayaan diri sosial dan disiplin religius siswa. Kebaruan penelitian terletak pada penerapan manajemen strategis sebagai sistem holistik dalam pendidikan karakter, mengatasi celah penelitian sebelumnya yang hanya berfokus pada kurikulum atau pedagogi tanpa mengkaji proses manajemen yang terintegrasi. Studi ini menawarkan model yang dapat direplikasi untuk sekolah dasar Islam, berkontribusi baik secara konseptual maupun praktis bagi pengembangan pendidikan karakter yang sistematis.